So in this equation the height is modeled by f(x) and the distance by x, so we can plug 2 in for f(x) and try to solve for x. So we have 2=26+2x-x^2, which can be changed into x^2-2x-24=0. Now we see if it is possible to turn this into (x-a)(x-b) form because if it is then, a and b are the answers unless one is negative, then it is ignored. In this case it is possible, because (x-6)(x+4) = x^2-2x-24, so the answer is 6 because -4 is negative. To check this answer we plug 6 into the original equation to see if we get 2. so 26+2(6)-(6)^2 = 26+12-36 = 38-36 = 2. Because the answer is 2, the answer is correct. Hope this helps!